Multidimensional factors associated with ADHD core symptoms in children: cognition, sleep, behavior, and demographics - Fu, Yanhong; Qin, Zixi; Qin, Ling; Zhang, Hong; Liu, Hairun; Huang, Siyan; Li, Dandan (Frontiers in Psychiatry, 2025)
ObjectiveAttention-Deficit/Hyperactivity Disorder (ADHD) involves inattention (IA) and hyperactivity-impulsivity (HI), which may be linked to distinct developmental and behavioral profiles. This study examined the demographic, cognitive, sleep, and behavioral factors associated with IA and HI symptoms among children.MethodsA cross-sectional sample of 331 children aged 6–12 years (mean = 8.72 ± 1.45 years; 84.6% male), diagnosed with ADHD, participated in this study between December 2020 and December 2022. ADHD symptoms were assessed via Swanson, Nolan, and Pelham Rating Scale-IV (SNAP-IV); cognitive function with Chinese version of the Das-Naglieri Cognitive Assessment System (DN: CAS); sleep via the Sleep Disturbance Scale for Children (SDSC); and behavior using the Conners Parent Symptom Questionnaire (PSQ).ResultsRegression analyses showed that HI symptoms were negatively associated with age (β = –0.197, p < 0.001) and higher in boys (β = –0.156, p = 0.004), while IA symptoms remained stable across age and gender. IA was significantly related to attentional deficits (β = –0.146, p = 0.037) and learning problems (β = 0.471, p < 0.001). HI showed stronger associations with conduct problems (β = 0.411, p < 0.001), sleep-wake disturbances (β = 0.164, p = 0.003), and low anxiety (β = –0.121, p = 0.033).ConclusionThese findings support dimension-specific understanding and targeted management of ADHD symptoms.